Homogeneous-heterogeneous reactions on Al2O3-Cu hybrid nanofluid flow over a shrinking sheet - Waini, Iskandar; Jamrus, Farah Nadzirah; Mohd Kasim, Abdul Rahman; Ishak, Anuar; Pop, Ioan (Penerbit Akademia Baru, 2022)
The effects of homogeneous-heterogeneous reaction on the fluid flow over a shrinking sheet is examined. A hybrid nanofluid is considered, with alumina and copper as the nanoparticles and water as the base liquid. The governing equations are solved numerically using similarity approach with the help of MATLAB software. Two outcomes are attained for several ranges of the mass flux parameter S. The friction factor as well as the concentration gradient enhances in the presence of nanoparticles, but the rate of heat transfer declines. Moreover, the concentration gradient is intensified for larger homogeneous and heterogeneous strength.